A digital microfluidic device with integrated nanostructured microelectrodes for electrochemical immunoassays1. Issue 18 (21st September 2015) - Rackus, Darius G.; Dryden, Michael D. M.; Lamanna, Julian; Zaragoza, Alexandre; Lam, Brian; Kelley, Shana O.; Wheeler, Aaron R.
<x xml:space="preserve">Abstract</x> Nanostructured microelectrodes (NMEs) combined with digital microfluidics (DMF) for automated electroimmunoassays.